Selection in trypanotolerant cattle breeds in Africa - Trail, J.C.M.; Feron, A.; Pelo, M.; Colardelle, C.; Ordner, G.; D'Ieteren, G.D.M.; Durkin, J.W.; Maehl, H.M.; Thorpe, W.R. (Institut National de la Recherche Agronomique, 1988)
Presents results of experiments to determine phenotypic & genotypic relationships of the abilities to control parasitaemia, resist anaemia or develop an immune response with animal performance in terms of daily weight gain, maintenance of packed cell volume levels and disease prevalence in trypanotolerant N'Dama and Sahiwal/Ayrshire cattle at three locations in Africa. Assesses heritability of each trypanotolerance-inducing characters.